The influence of financial knowledge and personality on financial management behavior of apliation based sturtup UMKM - Dwi Indi Febrianty; Dahrul Siregar (Institute of Computer Science (IOCS), 2023)
This study aims to determine the Effect of Financial Knowledge and Personality on Financial Management Behavior in Ulos Batak Crafts UMKM Based Sturtup in Medan City. The research method used is a quantitative method with an explanatory survey approach. The data collection technique used was simple random sampling with the Isaac and Michael formula and a sample of 62 UMKM Based Sturtup actors. The data analysis. Based on the results of the analysis, it was found that Financial Knowledge had a partial and significant effect on Financial Management Behavior, Personality had a partial and significant effect on Financial Management Behavior, and Financial Knowledge and Personality simultaneously had an effect and were significant on Financial Management Behavior UMKM Based Sturtup.